2018 18th International Conference on Harmonics and Quality of Power (ICHQP) 2018
DOI: 10.1109/ichqp.2018.8378918
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the performance between CFL and LED lamps under different voltage distortions

Abstract: Measurements have shown that the harmonic currents emitted by lamps with electronic ballast depend on the circuit topology and the existing supply voltage distortion. This paper quantifies the impact of supply voltage distortion on the harmonic and supraharmonic current emission of individual Light Emitting Diode (LED) lamps and compact fluorescent lamps (CFL). It also characterizes several Power Quality (PQ) parameters when those lamps are connected to pure sinusoidal waveform.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 12 publications
1
30
0
Order By: Relevance
“…Recent work on power quality issues caused by LED lamps, e.g., [1,27], has revealed the diversity in the LF current emissions of LED lamps. These variations are a consequence of the utilization of different LED driver circuits, and previous research has shown that, for the purpose of classification of the LF emissions of the line current waveform, LED lamps can be divided into four main categories [28].…”
Section: Led Lamp Setmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work on power quality issues caused by LED lamps, e.g., [1,27], has revealed the diversity in the LF current emissions of LED lamps. These variations are a consequence of the utilization of different LED driver circuits, and previous research has shown that, for the purpose of classification of the LF emissions of the line current waveform, LED lamps can be divided into four main categories [28].…”
Section: Led Lamp Setmentioning
confidence: 99%
“…A vital aspect of ongoing research in this area is the ability to model and simulate the low frequency (LF) current emissions (from DC to 2.5 kHz) of an enormous number of individual devices. Models of LED lamp high frequency (HF) emissions beyond the LF range are not considered in this paper but details of LED lamp HF distortion characteristics are available in [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…The Total Supraharmonic Current (TSHC) index was proposed by Grevener in [8], [12] for quantifying the supraharmonic emission over a frequency range. This index is based on Parseval's theorem [13] and has been used in other publications for analysis of supraharmonic distortion [2]. The TSHC is defined as follows:…”
Section: Calculating the Tshcmentioning
confidence: 99%
“…It has been shown in the literature that lighting emitting diode (LED) lamps emit more or less distortion in the supraharmonic range depending on their drivers' topology [2], [3], [7]. The characteristics of the supraharmonic emission from LED lamps have been presented in previous works: in [7], the grouping of frequency components over the whole supraharmonic range is used to quantify the distortion; in [6], the highest component over a frequency range is used.…”
Section: Introductionmentioning
confidence: 99%
“…The shape of the current waveform withdrawn by an energysaving lamp depends on the type of power factor correction applied [5]. It is also sensitive to the impedance of the supply system, the voltage total harmonic distortion and to the type of other loads connected onto the same network [6].…”
Section: B Conducted Electromagnetic Interference Of Household Loadsmentioning
confidence: 99%